The spirit of carnival : magical realism and the grotesque - Danow, David K. (David Keevin), 1944- (University Press of Kentucky, 2004)
The world of literature responds to the ""spirit of carnival"" in ways that are both social and cultural, mythological and archetypal. Literature provides a mirror in which carnival is reflected and refracted through the multifarious perspectives of verbal art. In his original, wide-ranging book, David K. Danow catches the various reflections in that mirror, from the bright, life-affirming magical side of carnival, as revealed in the literature of Latin American writers, to its dark, grotesque, death-embracing aspect as illustrated in numerous novels depicting the dire experience of the Second